2008
DOI: 10.15288/jsad.2008.69.896
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Aggression, Physical Aggression, and Injury in Nonpartner Relationships Among Men and Women in Treatment for Substance-Use Disorders

Abstract: ABSTRACT. Objective: This study focused on the prevalence and predictors of psychological aggression, physical aggression, and injury rates in nonintimate partner relationships in a substance-use disorder treatment sample. Method: The sample included 489 (76% men, 24% women) participants who completed screening measures for inclusion in a randomized control trial for an aggression-prevention treatment. Primary outcome measures included rates of past-year psychological aggression, physical aggression, and injur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
41
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 59 publications
7
41
0
4
Order By: Relevance
“…It is now well established in the literature that the use and abuse of substances is associated with the perpetration of violence (Boles & Miotto, 2003;Hoaken & Stewart, 2003;Moore et al, 2008). Between 60% and 75% of men and women in SUD treatment report perpetrating violence in the 12 months prior to interview, a rate that is considerably higher than that observed in community-based samples (Chermack, Fuller, & Blow, 2000;Murray et al, 2008). In their analysis of the National Treatment Improvement Evaluation Study (NTIES) data, one of the largest multi-site studies evaluating SUD treatment programmes, Burnette et al (2008) revealed that 72% of males and 51% of females reported a lifetime history of violence perpetration.…”
Section: Anger Among Individuals With Sudmentioning
confidence: 99%
See 2 more Smart Citations
“…It is now well established in the literature that the use and abuse of substances is associated with the perpetration of violence (Boles & Miotto, 2003;Hoaken & Stewart, 2003;Moore et al, 2008). Between 60% and 75% of men and women in SUD treatment report perpetrating violence in the 12 months prior to interview, a rate that is considerably higher than that observed in community-based samples (Chermack, Fuller, & Blow, 2000;Murray et al, 2008). In their analysis of the National Treatment Improvement Evaluation Study (NTIES) data, one of the largest multi-site studies evaluating SUD treatment programmes, Burnette et al (2008) revealed that 72% of males and 51% of females reported a lifetime history of violence perpetration.…”
Section: Anger Among Individuals With Sudmentioning
confidence: 99%
“…For instance, Walton, Chermack, and Blow (2002) found that individuals reporting more severe levels of psychological distress during treatment were most likely to continue to express violence post-treatment. Research has also emerged that suggests symptoms of depression play a role in the perpetration of violence among individuals with SUD (Chermack et al, 2009;Murray et al, 2008).…”
Section: Anger Among Individuals With Sudmentioning
confidence: 99%
See 1 more Smart Citation
“…There is an increasing awareness that substance use is associated with aggression and criminal violence in patients with cocaine dependence (Degenhardt, Day, Hall, Conroy, & Gilmour, 2005;Moeller et al, 1994;Murray et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A study on a community sample found that among individuals who were violent, substance use disorder (SUD) was a common diagnosis (Swanson, Holzer, Ganju, & Jono, 1990). Individuals in treatment for SUDs were more likely to engage in violent behavior than individuals in the general population (Murray et al, 2008). This link between violence and SUD is further emphasized by research done on individuals arrested for violent crimes.…”
Section: Violence and Substance Usementioning
confidence: 99%